A healthy public administration through healthy organizational practices - Mañas-Rodríguez, Miguel Ángel; Alcaraz-Pardo, Luis (Anales de Psicología / Annals of Psychology, 2016)
In the present study we have proposed a theoretical model based on Kopelman, Brief & Guzzo’s model (1990), in which transformational leadership is positioned as an antecedent of organizational climate, and the psychological capital, as a consequence of that climate. The theoretical model was tested using structural equations in a sample of 277 employees of a public Administration. The good fit of the data according to the revised goodness of fit indexes, both in the confirmatory analysis for each variable and in the structural model statistically validates our theoretical model, accepting the study hypotheses. This makes clear the need for the Administration to propose transformational leadership measures at the individual, team and organizational levels to strengthen the achievement of positive outcomes through positives organizational climate and psychological capital.